Segmental ATN in a Kidney with a Single Artery Transplanted from Living Related Donor - Uǧur, Ö; Caner, B.; Bakkaloǧlu, M.; Ergün, E. L.; Toklu, C.; Ahmadi, M. K.; Bekdik, C. (Nuklearmedizin - NuclearMedicine, 1996)
A sequential 99mTc-MAG3 renogram of a 20-year-old male who received a kidney from a living related donor is presented. Pre-transplant angiography of the donor showed the kidney had a single renal artery with upper and lower branches. The transplantation procedure was uneventful, allowing rapid simultaneous perfusion to the entire kidney. The first scan performed 2 days after the transplantation was normal except for retention of the radiotracer at the upper pole of the kidney. The renal collecting system was normal and no signs of dilatation or obstruction were noticed on ultrasonographic examination. A follow-up scan done on the 5th day of transplantation showed almost complete evacuation of the parenchymal retention previously seen on the upper pole of the kidney. This unusual finding was consistent with segmental acute tubular necrosis (ATN) of the upper pole of the kidney and showed that ATN might involve only a portion of a kidney in spite of the existence of a single artery of the transplant.In dieser Arbeit wird das Sequenzszintigramm mit 99mTc-MAG3 eines 20jährigen Patienten vorgestellt, der von einem lebenden Spender eine Niere erhalten hatte. Die präoperative Transplantât-Angiographie des Spenders zeigte, daß die zu transplantierende Niere nur eine einzige Nierenarterie hatte, welche Gefäßäste zum oberen und unteren Pol abgab. Die Transplantation war ohne Komplikationen verlaufen, die Trans-plantatzeichenperfusion gut. Die erste Sequenzszintigraphie wurde am zweiten Tag post op. durchgeführt und war normal, mit Ausnahme der Rentention des Radiotracers im oberen Pol. Das Nierenbecken-Kelchsystem war ebenfalls normal, und es konnten keine Anzeichen von Dilatationen der Obstruktionen während der Ultraschalluntersuchung wahrgenommen werden. Eine Nachuntersuchung mit 99mTc-MAG3 fünf Tage nach der Transplantation zeigte eine vollständige Entleerung der paren-chymalen Retentionen. Dieses ungewöhnliche Ergebnis war mit der segmentalen ATN des oberen Nierenpols vereinbar. Der Befund belegt, daß eine ATN nur einen kleinen Teil einer Niere involvieren kann, trotz der Existenz einer einzigen Arterie des Transplantats.
Keywords: Technetium-99m mercaptoacetyltriglycine; renal transplantation; acute tubular necrosis